Maximization of Site-Specific Solar Photovoltaic Energy Generation through Tilt Angle and Sun-Hours Optimization - Makenzi, Macben; Muguthu, Joseph; Murimi, Evan (Journal of Renewable Energy, 2020)
Many photovoltaic solar projects do not achieve optimum energy and power outputs due to poor technical sizing and system design approaches. Concerns on low-conversion rates, high intermittencies, and high-capital costs still haunt PV projects. The establishment of design methodologies that would result in increased outputs from solar arrays is crucial in addressing the aforementioned issues. The tilt angles of installed PV modules are critical factors that influence the power output of solar modules. Several resources are available that provide generic linear fits and estimation of tilt angles for various global regions. However, very few are capable of determining precise, location-specific tilt angles that would allow for optimal power output and energy generation. This paper presents a methodology developed to establish the optimum tilt angles for solar panels installed at specific locations, thus ensuring maximum energy generation. The modeling is based on the maximization of the solar irradiation incident on the surface of a PV panel by considering multiple site-specific variables. Different sets of transcendent equations have been derived which were used to calculate optimum tilt angles and the subsequent energy generation from specific configurations of photovoltaic arrays. The resulting algorithms were used to determine optimum tilt angles and energy generation for solar PV installations in Athi River, Kenya. Dynamic and static optimal tilt angles were compared with the region’s baseline industry practice of using a fixed tilt angle of 15◦. It was observed that the dynamic tilt angles improved the daily solar energy output by up to 6.15%, while the computed optimal static tilt angle provided a 2.87% output increment. This improvement presents a significant impact on the technical specification of the PV system with a consequent reduction in the investment and operational cost of such installations. It further demonstrated that the use of the optimum static tilt angle results in cost and space savings of up to 2.8% as compared to the standard industry practice. Additionally, 5.8% cost and space savings were attained by the utilization of dynamic tilt angles.